Retinoic Acid-Containing Liposomes for the Induction of Antigen-Specific Regulatory T Cells as a Treatment for Autoimmune Diseases - Daniëlle ter Braake (MDPI AG, 2021)
The current treatment of autoimmune and chronic inflammatory diseases entails systemic immune suppression, which is associated with increased susceptibility to infections. To restore immune tolerance and reduce systemic side effects, a targeted approach using tolerogenic dendritic cells (tolDCs) is being explored. tolDCs are characterized by the expression of CD11c, the major histocompatibility complex (MHC)II and low levels of co-stimulatory molecules CD40 and CD86. In this study, tolDCs were generated using a human-proteoglycan-derived peptide (hPG) and all-trans retinoic acid (RA). RA-tolDCs not only display a tolerogenic phenotype but also can induce an antigen-specific regulatory T cell (Treg) response in vitro. However, further analysis showed that RA-tolDCs make up a heterogeneous population of DCs, with only a small proportion being antigen-associated tolDCs. To increase the homogeneity of this population, 1,2-distearoyl-sn-glycero-3-phosphoglycerol (DSPG)-containing liposomes were used to encapsulate the relevant antigen together with RA. These liposomes greatly enhanced the proportion of antigen-associated tolDCs in culture. In addition, in mice, we showed that the liposomal co-delivery of antigen and RA can be a more targeted approach to induce antigen-specific tolerance compared to the injection of RA-tolDCs, and that these liposomes can stimulate the generation of antigen-specific Tregs. This work highlights the importance of the co-delivery of an antigen and immunomodulator to minimize off-target effects and systemic side effects and provides new insights in the use of RA for antigen-specific immunotherapy for autoimmune and chronic inflammatory diseases.